2017
DOI: 10.1007/s42001-017-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive perspectives on opinion dynamics: the role of knowledge in consensus formation, opinion divergence, and group polarization

Abstract: Two phenomena that are central to simulation research on opinion dynamics are opinion divergence-the result that individuals interacting in a group do not always collapse to a single viewpoint, and group polarization-the result that average group opinions can become more extreme after discussions than they were to begin with. Standard approaches to modeling these dynamics have typically assumed that agents have an influence bound, such that individuals ignore opinions that differ from theirs by more than some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 94 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…We speculate that the process of voting for the far right might lead to a delayed change in the political self-assessment of voters, but this remains an open avenue for upcoming research. Furthermore, given the strong performances of radical parties of various political colors and the diminishing strength of Europe's political center (in effect the flattening of election results to the benefit of the fringes) it becomes worthwhile to investigate how said self-political identification and acquiescence interacts with the growing polarization of electorates (Mueller and Tan, 2018, ). Increasing ideological divides among the public, as well as the trending mediatization of new cleavages (or confrontations between groups such as PEGIDA vs ANTIFA) speak to the growing discussion about so called 'echo-chambers' enabled by new social media, and their influence on political dialogue (Leeper, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the process of voting for the far right might lead to a delayed change in the political self-assessment of voters, but this remains an open avenue for upcoming research. Furthermore, given the strong performances of radical parties of various political colors and the diminishing strength of Europe's political center (in effect the flattening of election results to the benefit of the fringes) it becomes worthwhile to investigate how said self-political identification and acquiescence interacts with the growing polarization of electorates (Mueller and Tan, 2018, ). Increasing ideological divides among the public, as well as the trending mediatization of new cleavages (or confrontations between groups such as PEGIDA vs ANTIFA) speak to the growing discussion about so called 'echo-chambers' enabled by new social media, and their influence on political dialogue (Leeper, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the assumptions, different outcomes have been predicted. These include cases wherein the opinions of all agents converge to one, wherein several opinions are juxtaposed, and wherein extreme opinions or polarizations emerge [58][59][60][61][62][63][64][65][66].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Schmidt et al have found by evaluating the users' attitude toward the vaccination on Facebook that the content consumption related to the vaccine is mainly determined by the echo chamber effect, and the polarization phenomenon has become increasingly obvious over time. Mueller and Tan believed that in a one‐dimensional opinion space, drift and collapse are almost inevitable, and the behavior at group‐level is related to the formation of consensus, stable disagreement, and group polarization, even without the consideration of limited impact or stubborn extremists. Fu and Zhang proposed an individual‐based biased assimilation model to study the opinions trend on connected social networks.…”
Section: Literature Reviewmentioning
confidence: 99%